2019
DOI: 10.1111/anec.12641
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific clinical outcomes after cardiac resynchronization therapy in left bundle branch block‐associated idiopathic nonischemic cardiomyopathy: A NEOLITH II substudy

Abstract: Background: Sex differences in clinical outcomes for left bundle branch block (LBBB)associated idiopathic nonischemic cardiomyopathy (NICM) after cardiac resynchronization therapy (CRT) are not well described. Methods: A retrospective cohort study at an academic medical center included subjects with LBBB-associated idiopathic NICM who received CRT. Cox regression analyses estimated the hazard ratios (HRs) between sex and clinical outcomes. Results: In 123 total subjects (mean age 62 years, mean initial left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…CRT-D may confer greater benefits to women than to men in the setting of NICM and LBBB. 175 , 176 , 177 , 178 Subgroup analysis of the M ulticenter A utomatic D efibrillator I mplantation T rial With C ardiac R esynchronization T herapy (MADIT-CRT) study identified women as exceptional responders to CRT, with a 72% decrease in all-cause mortality and greater reduction in left atrial and ventricular volumes. 178 Despite men typically being younger at diagnosis, in a retrospective study conducted by Wang et al., women were found to have a lower risk of death, compared with men in LBBB-associated NICM, after controlling for age at diagnosis.…”
Section: Nonacute Presentations: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CRT-D may confer greater benefits to women than to men in the setting of NICM and LBBB. 175 , 176 , 177 , 178 Subgroup analysis of the M ulticenter A utomatic D efibrillator I mplantation T rial With C ardiac R esynchronization T herapy (MADIT-CRT) study identified women as exceptional responders to CRT, with a 72% decrease in all-cause mortality and greater reduction in left atrial and ventricular volumes. 178 Despite men typically being younger at diagnosis, in a retrospective study conducted by Wang et al., women were found to have a lower risk of death, compared with men in LBBB-associated NICM, after controlling for age at diagnosis.…”
Section: Nonacute Presentations: Diagnosis and Treatmentmentioning
confidence: 99%
“…178 Despite men typically being younger at diagnosis, in a retrospective study conducted by Wang et al., women were found to have a lower risk of death, compared with men in LBBB-associated NICM, after controlling for age at diagnosis. 176 Women have a shorter baseline QRS duration (QRSd) and smaller LV volumes than men. Therefore, women have relatively more dysynchrony for any prolonged QRSd, which may contribute to a better outcome with CRT.…”
Section: Nonacute Presentations: Diagnosis and Treatmentmentioning
confidence: 99%